Unbounded solution for a fractional boundary value problem - Guezane-Lakoud, Assia; Kilicman, Adem (SpringerOpen, 2014)
This paper concerns the existence of unbounded positive solutions of a fractional boundary value problem on the half line. By means of the properties of the Green function and the compression and expansion fixed point theorem (Kwong in Fixed Point Theory Appl. 2008:164537, 2008), sufficient conditions are obtained to guarantee the existence of a solution to the posed problem.